KOMUNIKASI VISUAL DI ERA DIGITAL MELALUI PELATIHAN FOTOGRAFI - Wulan Purnama Sari; Lydia Irena (Jurnal Bakti Masyarakat Indonesia, 2021)
The existence of educational institutions plays a very large role in educating human resources in Indonesia. Because in essence education has two main objectives, namely to help educate humans and make intelligent humans become good. Not only intellectually intelligent but also have a strong character, especially to face the times and globalization. Therefore the role of educational institutions must also pay attention to the development of students in the scope of soft skills by equipping them with practical skills. Photography is an important part of visual communication which is now an integral part of people's lives. Coupled with the trend of social media, human life is centered in it. So that this PKM activity aims to be a form of education for students regarding the function of photography in today's digital era. The method used in PKM activities is to conduct training for partners with student and female participants. PKM activities are carried out online using the Zoom application. The results of PKM activities indicate an increase in participants' understanding of photography, which can be seen through the pre and post PKM activity questionnaires. In addition, participants also have an interest in photography in the scope of social media, including photography techniques and recommendations for editing applications using smartphones. Suggestions from the team regarding this activity are to carry out further activities that focus on photography using smartphones for upload needs on social media.ABSTRAK:Keberadaan lembaga pendidikan sangat besar peranannya dalam mencerdaskan sumber daya manusia di Indonesia. Sebab pada hakikatnya pendidikan memiliki dua tujuan utama yaitu membantu mencerdaskan manusia dan menjadikan manusia cerdas tersebut menjadi baik. Tidak hanya cerdas secara intelektual tetapi juga memiliki karakter yang kuat, terutama untuk menghadapi perkembangan zaman dan globalisasi. Oleh karenanya peran lembaga pendidikan juga harus memperhatikan pengembangan peserta didik dalam ruang lingkup soft skill dengan membekali mereka keterampilan yang bersifat praktis. Fotografi menjadi bagian penting dalam komunikasi visual yang sekarang ini menjadi salah satu bagian integral dalam kehidupan masyarakat. Ditambah juga dengan adanya tren media sosial yang menjadikan kehidupan manusia berpusat di dalamnya. Sehingga kegiatan PKM ini bertujuan untuk menjadi bentuk edukasi bagi para siswa terkait fungsi fotografi di era digital saat ini. Metode yang digunakan dalam kegiatan PKM adalah dengan melakukan pelatihan kepada pihak mitra dengan peserta siswa dan siswi. Kegiatan PKM dilaksanakan secara daring dengan menggunakan aplikasi Zoom. Hasil kegiatan PKM menunjukkan adanya peningkatan pemahaman peserta mengenai fotografi, yang dapat dilihat melalui kuesioner pra dan paska kegiatan PKM. Selain itu, peserta juga memiliki ketertarikan terhadap fotografi dalam lingkup media sosial, termasuk didalamnya teknik fotografi dan juga rekomendasi aplikasi editing dengan menggunakan smartphones. Saran dari tim terkait kegiatan ini adalah dilaksanakannya kegiatan lanjutan yang berfokus pada fotografi dengan menggunakan smartphones untuk kebutuhan unggah di media sosial.